Educação do campo e salas multisseriadas: desafios e possibilidades de integração curricular - Souza, Aline da Costa de (2025)
This study aims to identify the challenges and opportunities of multigrade classrooms in a school serving the first cycle of elementary education in Mogi das Cruzes/SP, focusing on the articulation between the city’s prescribed curriculum and daily school practices. The research draws on the studies of Freire (2004), Arroyo (1999), Molina (2006), and Souza (2018) on the conceptions of education of and in rural areas, acknowledging the need to differentiate purposes and intentions of such conceptions. Contributions from Tardivo (2023) and Hage (2018) were crucial in characterizing the organization of multigrade classrooms and addressing the associated challenges and possibilities. In the field of curriculum, the research is grounded in the works of Sacristán (1998) and Macedo (2022), which deepened our understanding of curricular dynamics in its production and implementation. These studies guided our investigation into the school environment and the curricular perspective under which the school operates, contributing to the improvement of educational quality. The Municipal Curriculum of Mogi das Cruzes and its Management Plan were fundamental in identifying the municipality's curriculum conceptions. Teacher education was explored through the perspectives of Feldmann (2009), Freire (2004), and Tardif (2007), to connect curricular theory with pedagogical practice through teacher training. The research employed a framework of document analysis, semi-structured interviews with teachers and school administrators, observations, and records from the studied school. The final considerations highlight the importance of strengthening teacher training and promoting the connection between curriculum and pedagogical practices, showing that adapting the curriculum to the context of multigrade classrooms can significantly enhance educational quality. The study underscores the need for continuous dialogue between educational policies and the realities of schools to ensure the right to equitable and inclusive education